Disentangling the trajectories of alpha, beta and gamma plant diversity of North American boreal ecoregions since 15,500 years - Blarquez, Olivier; Carcaillet, Christopher; Frejaville, Thibaut; Bergeron, Yves (Frontiers in Ecology and Evolution, 2014)
Assessment of biodiversity in a changing world is a key issue and studies on the processes and factors influencing its history at relevant time scales are needed. In this study, we analysed temporal trends of plant diversity using fossil pollen records from the North American boreal forest-taiga biome (NABT). We selected 205 pollen records spanning the last 15,500 years. Diversity was decomposed into α and γ richness, and β diversity, using Shannon entropy indices. We investigated temporal and spatial patterns of β diversity by decomposing it into independent turnover (variation in taxonomic composition due to species replacements) and nestedness (variation due to species loss) components. The palynological diversity of the NABT biome experienced major rearrangements during the Lateglacial and early Holocene in response to major climatic shifts. The β nestedness likely reflected plant immigration processes and generally peaked before the β turnover value, which mirrors spatial and temporal community sorting related to environmental conditions and specific habitat constraints. Palynological diversity was generally maximal during the Lateglacial and the early Holocene and decreased progressively during the Holocene. These results are discussed according to macro-ecological processes, such as immigration, disturbances and environmental fluctuations, with climate most notably as the main ecological driver at millennial scales.